The Relationship Between the Distance from University and the Participation of INTI International University Students - Leong, X.L.; Lim, K.Y.; Yeoh, L.B.H.; Phang, K.S.; Wong, C.K.; Koh, W.S. (INTI International University, 2018)
This study aims to analyze the statistical relationship between the distance from INTI International University and how it affects students’ participation of university’s activities. Descriptive and inferential statistical methods are applied in this study. From this study, it is generally understood that the perception of students towards the importance of university’s activities is relatively neutral. The number of clubs joined is relatively small and there exists cases of absenteeism and lateness. The mean distance from residence to University is relatively short at 14 minutes as most students live at the hostel or nearby private residences. Therefore, it can be noted that distance is not a determining factor for students’ participation in University activities.